Mitochondria damage and ferroptosis involved in Ni-induced hepatotoxicity in mice. (30th January 2022) - Wei, Ling; Zuo, Zhicai; Yang, Zhuangzhi; Yin, Heng; Yang, Yue; Fang, Jing; Cui, Hengmin; Du, Zongjun; Ouyang, Ping; Chen, Xia; Chen, Jian; Geng, Yi; et al.
Graphical abstract: Highlights: High doses of NiCl2 induces liver damage in mice. NiCl2 induces mitochondrial damage in the liver of mice. NiCl2 induce ferroptosis by inducing mitochondrial damage and down-regulating ferritin. Abstract: Nickel (Ni) is an environmental toxicant that can cause toxic damage to humans and animals. Although the hepatotoxicity of Ni has been confirmed, its precise mechanism is still unclear. In this study, the results showed that nickel chloride (NiCl2 )-treatment could induce mice hepatotoxicity including hepatic histopathological alterations and up-regulation of serum AST and ALT. According to the results, NiCl2 increased malondialdehyde (MDA) production while reducing total antioxidant capacity (T-AOC) activity and glutathione (GSH) content. Additionally, NiCl2 induced mitochondrial damage which was featured by increase in mitochondrial ROS (mt-ROS) and mitochondrial membrane potential (MMP) depolarization. The mitochondrial respiratory chain complexes I-IV and ATP content were decreased in the liver of NiCl2 -treated mice. Meanwhile, NiCl2 caused hepatic ferroptosis accompanied by increased iron content in the liver and up-regulation of cyclooxygenase 2 (COX-2) protein and mRNA expression levels, down-regulation of glutathione eroxidase 4 (GPX4), ferritin heavy chain 1 (FTH1) and nuclear receptor coactivator 4 (NCOA4) protein and mRNA expression levels. Altogether, the above mentioned results indicate that NiCl2 treatment may induce hepatic damage through mitochondrial damage and ferroptosis.